Place Attachment of Entrepreneurs: A Proposed Analytical Framework - Gebyar Ayuningtyas; Happy Ratna Santosa; Dewi Septanti (IPTEK Journal of Proceedings Series, 2020)
In recent years, home-based enterprises have been giving significant implications for the economic improvement of the middle-low income community in Surabaya. With all of the limitations that exist, space, complex activities, and community acceptance become predictors that influence the formation of people-place relationship. Previous studies that tend to focus on the use of space are less concerned with the interaction undertaken by entrepreneurs which make them choose to continue their business where they have started. The dynamics of daily life in shaping social relations and functionality of place will affect how entrepreneurs perceive and assess their home-environment. Thus, it is important to highlight the process of the emerging attachment related to the use of a home for generating additional income. As the nature of place attachment which is multidisciplinary and socially constructed, this paper provides reviews on different paradigms, conceptualizations, and attachment types that should be used as analytical frameworks in the context of productive housing. A rich literature study aims to give further insight without ignoring the natural settings of the research context. By emphasizing the role of life experience of entrepreneurs, a more fruitful understanding towards accumulative assessment and perceived environment that triggers place attachment could be obtained in the future research.